Lower Order of Entire Functions of Several Complex Variables - Satendra Kumar, Majid Hamid Dar (Mathematical Statistician and Engineering Applications, 2022)
In the present paper, we study the growth properties of entire functions of several complex variables. The characterizations of generalized lower order of entire functions of several complex variables have been obtained in terms of their Taylor’s series coefficients. Also we have obtained the characterization of generalized lower order of entire functions of several complex variables in terms of approximation and interpolation errors.